(Increasing the Eugenol Content of Clove Leaf Oil by Rectification) - Sudibyo, Agus; Bastaman, Syarief; -, Hendarti (Warta Industri Hasil Pertanian, 1987)
A study on rectifications of clove leaf oil had been conducted in order to improve its quality and eugenol content. Retifications was done by distillation using low vacuum pressure (5 and 15 mm Hg) and resulted in two fractions of clove leaf oil (fraction I and II). Observation was emphasized on the eugenol content and its quality. The eugenol content of fraction I was increased by 5-8% and those of fraction II was 30-31%. As for the purity of eugenol content, it was decreased in fraction I, and increased in the other.